Enhanced NEMO protocol to achive seamless handoff - Islam, Shayla (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
In order to support mobile network, a management mechanism of Network Mobility Basic Support Protocol (NEMO BSP) has been standardized by Information Engineering Task Force (IETF). NEMO BSP is an extension of Mobile IPv6 (MIPv6) and inherits all the shortcomings like higher handoff latency, packet loss etc. As Network Mobility (NEMO) is engagedto manage the movement of Mobile Router (MR) and it's Mobile Network Nodes (MNNs) during handoff, it is very important to improve the performance of mobility management protocol to achieve seamless handoff with lower delay and packet loss in NEMO environment.The diversity of location of different nodes and complexity of NEMO route optimization procedure result in several rounds of signaling messages. Also longer time is required to complete handoff process which may cause performance degradation of the applications running on Mobile Network Nodes (MNNs). Additionally, when a change in point of attachment of the mobile network is accompanied by a sudden burst of signaling messages, "Signaling Storm" occurs and it ultimately results in temporary congestion, handoffdelays, or even packet loss. This effect is especially noteworthy for wireless environment where bandwidth is relatively limited. Therefore providing uninterrupted Internet connection, applying route optimization and multihoming technique in NEMOare becoming most significant areas for current researchers. In case of Mobile IPv6 network, Fast Handover Scheme for Hierarchical Mobile IPv6 (FHMIPv6) works successfully as a host mobility solution. However,in NEMO environment applying FHMIPv6 mechanism is a challenging task asboth MR and its MNNs need to be considered. The aim of this research is to enhance mobility management mechanisms in NEMO environment with the intention of establishing uninterrupted Internet connectionduring handoff. It proposes a Macro Mobility Scheme (MM-NEMO)in NEMO networkin order to achieve the seamless handoff. This is achieved by integrating improved FHMIPv6 scheme with NEMO networks. Theperformance of the proposed scheme is evaluated using both analyticaland simulation approaches. The proposed scheme is benchmarked with the standard NEMO BSP. The performance metrics used for analytical evaluation are location update cost, packet delivery cost and cell residence time respectively. The analytical result shows that the total handoff cost for the proposed scheme is lower than that of NEMO-BSP. The simulation is done using Network Simulator (NS-2). The simulation result shows that the proposed scheme outperforms the standard NEMO BSP in terms of packet loss (less than 6%) and handoff latency(reduced to 42%).